Effect of Tiaoxin Recipe on Memory Learning and Synaptic Plasticity in APP/PS1 Double Transgenic Alzheimer's Disease Mice based on αCaMKⅡ-CREB-BDNF Signal Pathway - Xiaowen WANG; Hong QIAN; Chunjuan SHEN; Yanjun LI; Haixin YUAN; Jian WANG (康复学报)
Objective:To observe the effects of Tiaoxin recipe on long-term potentiation (LTP) in hippocampal CA1 region, hippocampal alpha calcium/calmodulin-dependent kinaseⅡ (αCaMKⅡ), cyclic adenosine monophosphate response element binding protein (CREB), brain derived neurotrophic factor (BDNF), postsynaptic density 95 (PSD-95) mRNA and protein expression in hippocampal CA1 region of APP/PS1 double transgenic mice. To explore the mechanism of Tiaoxin recipe in improving memory learning and synaptic plasticity in APP/PS1 double transgenic AD mice from the point of view of αCaMKⅡ-CREB-BDNF signal pathway.Methods:A total of 54 3-month-old APP/PS1 male mice were randomly divided into the model group, the Tiaoxin recipe group and the Donepezil group according to the method of random number table, with 18 cases in each group. Another 18 C57/BL6 male wild type mice of the same age and the same strain were set as the normal group. According to the conversion standard of equivalent dose between animal and human in pharmacological test, the drug dose was converted according to human equivalent dose (body mass:60 kg) in Donepezil group and Tiaoxin recipe group. The mice in the normal group and the model group were given the same amount of normal saline 10 mL/ (kg·d), the Donepezil group was given Donepezil hydrochloride at a dose of 0.05 mg/ (kg·d), and the Tiaoxin recipe group was given Tiaoxin recipe granules by gastric perfusion at a dose of 0.057 g/ (kg·d). The mice in the four groups were given intragastric administration at the age of three months, once a day for three months, Electrophysiological technique was used to induce LTP in hippocampal CA1 region of four groups of mice in vitro. Real-time fluorescence quantitative PCR (RT-qPCR) was used to detect the expression of αCaMKⅡ, CREB, BDNF and PSD-95mRNA in hippocampal hippocampus of mice in four groups, and Western blotting (WB) was used to detect the expression of paired p-αCaMKⅡ, p-CREB, BDNF and PSD-95 in hippocampus of four groups of mice.Results:①Electrophysiological results: under the intensity of 0.1-0.7 mA stimulation, there was no significant difference in the slope of hippocampal I/O curve among the four groups (P>0.05). Under the interval of 20-250ms stimulation, there was no significant difference in PPF facilitation among the four groups (P>0.05). During the 50-60 min stable period, compared with the model group, the slope of fEPSP in the LTP induced by Tiaoxin recipe group was significantly higher than that in the model group (P<0.05).②RT-qPCR results: compared with the normal group, the expressions of αCaMKⅡ, CREB, BDNF and PSD-95mRNA in the hippocampus of the model group were significantly lower, and the difference was statistically significant (P<0.05). Compared with the model group, the expressions of αCaMKⅡ, CREB, BDNF and PSD-95mRNA in the hippocampus of the Tiaoxin recipe group were significantly higher, and the difference was statistically significant (P<0.05).③Western blot assay results: Compared with the normal group, the expressions of p-αCaMKⅡ, p-CREB, BDNF and PSD-95 protein in the hippocampus of the model group were significantly lower, and the difference was statistically significant (P<0.05). compared with the model group, the expressions of p-αCaMKⅡ, p-CREB, BDNF and PSD-95 prote in in the hippocampus of mice in Tiaoxin recipe group were significantly increased, and the difference was statistically significant (P<0.05).Conclusion:Tiaoxin recipe can improve the LTP of hippocampal CA1 region of APP/PS1 double transgenic AD mice, increase the expression of PSD-95mRNA and protein, improve the memory learning function and synaptic plasticity of APP/PS1 double transgenic AD mice, and its mechanism may be related to its up-regulation of hippocampal αCaMKⅡ-CREB-BDNF signal pathway.